2002
DOI: 10.1042/bj20011612
|View full text |Cite
|
Sign up to set email alerts
|

Antizyme induction by polyamine analogues as a factor of cell growth inhibition

Abstract: The polyamines spermidine and spermine and their diamine precursor putrescine are essential for mammalian cell growth and viability, and strategies are sought for reducing polyamine levels in order to inhibit cancer growth. Several structural analogues of the polyamines have been found to decrease natural polyamine levels and inhibit cell growth, probably by stimulating normal feedback mechanisms. In the present study, a large selection of spermine analogues has been tested for their effectiveness in inducing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
43
0
1

Year Published

2005
2005
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(49 citation statements)
references
References 34 publications
5
43
0
1
Order By: Relevance
“…Interestingly, cyclin D1 was also diminished in these cells whereas cyclin A levels were not affected. Similar results were found in rat HTC cells (data not shown), a cell line commonly used for studies on the antizyme and AZI pathways (Mitchell et al, 2002;Murakami et al, 1996). Thus, levels of cyclin D1 decrease when AZI expression is suppressed.…”
Section: Effect Of Azi Overexpression On Cell Proliferation and Transsupporting
confidence: 73%
“…Interestingly, cyclin D1 was also diminished in these cells whereas cyclin A levels were not affected. Similar results were found in rat HTC cells (data not shown), a cell line commonly used for studies on the antizyme and AZI pathways (Mitchell et al, 2002;Murakami et al, 1996). Thus, levels of cyclin D1 decrease when AZI expression is suppressed.…”
Section: Effect Of Azi Overexpression On Cell Proliferation and Transsupporting
confidence: 73%
“…In addition to its role in regulating ODC activity and degradation, antizyme was also demonstrated to regulate polyamine transport across the plasma membrane via a yet unknown mechanism Mitchell et al, 1994;Suzuki et al, 1994;Sakata et al, 2000). In accordance with these observations, recent studies have established that Az may act as a tumor suppressor, as its induction is associated with growth inhibition (Mitchell et al, 2002), while its overexpression increases apoptosis and reduces tumorigenesis (Feith et al, 2001;Fong et al, 2003).…”
Section: Introductionmentioning
confidence: 90%
“…29 Studies by several other groups have demonstrated that inhibition of ODC by DFMO led to G 1 arrest in a variety of cell lines including tumor cells. [30][31][32] Both oligoamines and BENSpm profoundly decrease ODC activity within 24 h in MCF-7 cells, potentially through the activation of the ODC inhibitor, antizyme (AZ), 18,33 implying that downregulation of ODC could be one mechanism leading to G 1 arrest. In contrast, CHENSpm differs from BENSpm only at the terminally modified cycloheptylmethyl group, but leads to a G 2 /M arrest.…”
Section: Growth Inhibition and Cell Cycle Arrest By Polyamine Analoguesmentioning
confidence: 99%